Identification of novel catabolic genes involved in 17β‐estradiol degradation by Novosphingobium sp. ES2‐1. (26th March 2021) - Li, Shunyao; Sun, Kai; Yan, Xin; Lu, Chao; Waigi, Michael Gatheru; Liu, Juan; Ling, Wanting
Summary: Novosphingobium sp. ES2‐1 is an efficient 17 β ‐estradiol (E2)‐degrading bacterium, which can convert E2 to estrone (E1), then to 4‐hydroxyestrone (4‐OH‐E1) for subsequent oxidative cracking. In this study, the molecular bases for this process were elucidated. Two novel monooxygenase systems EstP and EstO were shown to catalyse the oxygenation of E1 and 4‐OH‐E1, respectively. EstP was a three‐component cytochrome P450 monooxygenase system consisting of EstP1 (P450 monooxygenase), EstP2 (ferredoxin) and EstP3 (ferredoxin reductase). Ultraperformance liquid chromatography‐high resolution mass spectrometry (UPLC‐HRMS) analysis revealed that EstP catalysed the 4‐hydroxylation of E1 to produce 4‐OH‐E1. The resultant 4‐OH‐E1 was further oxidized by a two‐component monooxygenase system EstO consisting of EstO1 (flavin‐dependent monooxygenases) and EstO2 (flavin reductase). UPLC‐HRMS combined with 1 H‐nuclear magnetic resonance analysis demonstrated that EstO catalysed the breakage of C9‐C10 to yield a ring B‐cleavage product. In addition, the oxygenase component genes estP1 and estO1 exhibited contrary inductive behaviours when exposed to different steroids, suggesting that EstP1‐mediated 4‐hydroxylation was E2‐specific, whereas EstO1‐mediated monooxygenation might be involved in the degradation of testosterone, androstenedione, progesterone and pregnenolone. This also implied that the mechanisms of the catabolism of different steroids by the same microorganism might be partially interlinked. Abstract :